Venice Variations Tracing the Architectural Imagination (University College London, 2018)
From the myth of Arcadia through to the twenty-first century, ideas about sustainability - how we imagine better urban environments - remain persistently relevant, and raise recurring questions. How do cities evolve as complex spaces nurturing both urban creativity and the fortuitous art of discovery, and by which mechanisms do they foster imagination and innovation? While past utopias were conceived in terms of an ideal geometry, contemporary exemplary models of urban design seek technological solutions of optimal organisation. The Venice Variations explores Venice as a prototypical city that may hold unique answers to the ancient narrative of utopia. Venice was not the result of a preconceived ideal but the pragmatic outcome of social and economic networks of communication. Its urban creativity, though, came to represent the quintessential combination of place and institutions of its time. Through a discussion of Venice and two other works owing their inspiration to this city - Italo Calvino's Invisible Cities and Le Corbusier's Venice Hospital - Sophia Psarra describes Venice as a system that starts to resemble a highly probabilistic 'algorithm'. The rapidly escalating processes of urban development around our big cities share many of the motivations for survival, shelter and trade that brought Venice into existence. Rather than seeing these places as problems to be solved, we need to understand how urban complexity can evolve, as happened from its unprepossessing origins in the marshes of the Venetian lagoon to the 'model city' enduring a 1000 years. This book frees Venice from stereotypical representations, revealing its generative capacity to inform potential other 'Venices' for the future. Praise for The Venice Variations 'Psarra animates the city as a creature that is based on the dialogue between anonymous collective and branded individual imagination. It reconstitutes the principles and ways of thinking that allowed Venice to act as a source of inspiration... It shows us how the natural city, and its mythological plots that we have in our minds, are being embodied in an open creativity. The book can be purchased in classic print or purchased electronically at no cost.' slus.gr '...a visual treat that is made more accessible and meaningful through the diagrams.' Archido From the myth of Arcadia through to the twenty-first century, ideas about sustainability - how we imagine better urban environments - remain persistently relevant, and raise recurring questions. How do cities evolve as complex spaces nurturing both urban creativity and the fortuitous art of discovery, and by which mechanisms do they foster imagination and innovation? While past utopias were conceived in terms of an ideal geometry, contemporary exemplary models of urban design seek technological solutions of optimal organisation. The Venice Variations explores Venice as a prototypical city that may hold unique answers to the ancient narrative of utopia. Venice was not the result of a preconceived ideal but the pragmatic outcome of social and economic networks of communication. Its urban creativity, though, came to represent the quintessential combination of place and institutions of its time. Through a discussion of Venice and two other works owing their inspiration to this city - Italo Calvino's Invisible Cities and Le Corbusier's Venice Hospital - Sophia Psarra describes Venice as a system that starts to resemble a highly probabilistic 'algorithm'. The rapidly escalating processes of urban development around our big cities share many of the motivations for survival, shelter and trade that brought Venice into existence. Rather than seeing these places as problems to be solved, we need to understand how urban complexity can evolve, as happened from its unprepossessing origins in the marshes of the Venetian lagoon to the 'model city' enduring a 1000 years. This book frees Venice from stereotypical representations, revealing its generative capacity to inform potential other 'Venices' for the future. Praise for The Venice Variations 'Psarra animates the city as a creature that is based on the dialogue between anonymous collective and branded individual imagination. It reconstitutes the principles and ways of thinking that allowed Venice to act as a source of inspiration... It shows us how the natural city, and its mythological plots that we have in our minds, are being embodied in an open creativity. The book can be purchased in classic print or purchased electronically at no cost.' slus.gr '...a visual treat that is made more accessible and meaningful through the diagrams.' A Daily Dose of Architecture Books